Predicting university faculties switching intention to bioplastic products in an emerging economy: A step toward sustainable future - Islam, Md. Afsarul; Karim, B.M. Sajedul; Uddin, Md. Emran; Dhir, Md. Gulam Mokta; Haque, Md. Alaul (YAYASAN MITRA PERSADA NUSANTARA, 2023)
This study is undertaken to examine the university faculties switching intention to bioplastic (SIB) products with the help of the Theory of Reasoned Action (TRA) along with three additional constructs namely Green Knowledge (GK), Environmental Concern (EC), and Person’s Innovativeness (PI). Importantly, this study is quantitative in nature whereas a structured questionnaire was placed to collect the data from 218 survey respondents. SPSS 25 had been used to analyze the reliability of the constructs, correlation, and regression to find out the direct effect of predictors on university faculties switching intention to bioplastic products. This study reveals that attitude towards bioplastic, green knowledge, environmental concern, and person’s innovativeness have statistically significant relationships with the switching intention to use bioplastic products. Surprisingly, in this study person’s innovativeness had found the strongest predictor among all the studied constructs. This study contributes theoretically to the robustness of the Theory of Reasoned Action (TRA) with Green Knowledge (GK), Environmental Concern (EC), and Person’s Innovativeness (PI) in academic perspectives. Moreover, the outputs of this study help the bioplastic manufacturing firms to produce bioplastic products in bulk amount in future and uptake the market of bioplastic products in Bangladesh.